UN Cybercrime Treaty: A Menace in the Making - Brown, Deborah (Human Rights Watch, 2023)
Governments are meeting in Vienna this week to negotiate a global treaty on cybercrime. But instead of fostering cooperation in cybercrime, the treaty may end up facilitating cross-border repression and make it more difficult to investigate actual cybercrimes.
Keywords: 2023-10 October